Failure modes and buckling coefficient of partially stiffened cold-formed sections in bending. (August 2015) - Maduliat, S.; Mendis, P.; Ngo, T.D.
Abstract: Flange edge stiffeners increase the ultimate moment capacity of cold-formed channel sections. At the same time, they cause complexity to the buckling failure mode of the section. There is a lack of experimental research on the failure mode of sections with a partially stiffened element, such as channel sections with edge stiffeners, in which a distortional buckling mode can be observed. The focus of recent studies is mainly on the behaviour of the whole section as one member under bending without any concern about the relationship between the web and flange ratio. In this study, an extensive experimental analysis of 42 cold-formed channel sections was used to explore the failure behaviour of cold-formed channel sections under pure bending. The sections were made from cold-formed G450 steel with a nominal thickness of 1.6 mm. The results of the pure bending experimental investigations are used to describe the relationship between the web and flange ratio and the failure deformations. It is also shown that the current international cold-formed steel specifications over-predict the buckling coefficient of partially stiffened elements with high aspect ratio values. The experimental results are used to propose revisions to current international cold-formed steel specifications. Highlight: We tested 42 cold-formed channel sections in bending. We described the relationship between the web and flange ratio and the failure deformations of channel sections. We compared the test results with current international standards. We found that the current specifications are unduly conservative for partially stiffened and high aspect ratio elements. We proposed modification to current international cold-formed steel specifications.